Perception of adolescents and mothers towards obesity and factors affecting obesity in Sek. Men. Paduka Tuan, in Segamat, Johor, 1996 - Surinah Asan,; Hanafiah Mohd Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
The prevalens of obesity among adolescents is a health problem which is on the increase in Malaysia. Hence, in an attempt to prevent and control the problem, we need to study the factors associated with adolescents obesity especially perceptions towards it. Therefore, a case control study was conducted at Sekolah Menengah Paduka Tuan, Segamat in February 1996. The prevalence of obesity among the students in this school is 7.2%. Students with BMl 25 were classified as cases (138 students) and students with BMI <25 and were matched one to one by the classroom as the control group. The data collection was carried out by measuring the weight (kg) and height (m) and self-administered questionnaires were given to the students and their mothers. The result of this study shows the perception of adolescents (case) towards obesity were mainly positive in 88.0% and 92.0% among control. The perception of students towards the body status were statistically significant (p<0.05). Among the obese adolescents who did not perceived themselves as obese, the chances of getting obes is 12 times higher than obes adolescents who perceived themselves as obese with the odds ratio is 12.57 (5.55-26.8). Adolescents who have regular physical exercise will be protected from getting obesity, where the p < 0.05 and the odd~ ratio 0.43 (0.24- 0.78). The family history of obesity as a biological factor were found in 92.0 % of cases and 52.2 % controls. This factor has astatistically significant relation with the prevalens of obesity (p<0.05) with the odds ratio of 10.53 and the confident interval" is 4.43 -25.88. Therefore, adolescents who have family history of obesiti will have higher risk of getting obesity about 10 time compared to adolescents with no family history .